2021
DOI: 10.21608/mjppf.2021.149209
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Promising Hybrid Rice Genotypes Under Different Irrigation Intervals

Abstract: Water shortage stress is the most critical abiotic factor reducing rice yield. Water deficit stress at whichever of the rice critical growth stage causes decline in yield. A field experiment was conducted at the Experimental Farm of Sakha Agricultural Research Station, Kafrelsheikh, Egypt during 2018 and 2019 seasons, to investigate the effect of four irrigation intervals (continuous flooding(I1), irrigation every six days(I2), nine days(I3) and twelve days(I4)) on performance of five genotypes (Giza 178, IR 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
1
1
1
Order By: Relevance
“…On the other hand, the highest value of number of unfilled grains panicle-1 produced by ARD6-8-1-1-1-1-5 under drought treatment , while the lowest value of number of unfilled grains panicle-1 produced by Nerica 7 and Egyptian Yasmin under Normal irrigation. These results are in harmony with those stated by Hashem et al (2016), Zaman et al (2018) and Gewaily et al (2021) who reported that water deficit induced several changes in the structure and functional processes of reproductive organs in the rice, resulting to fluctuations in fertilization or premature abortion of the seed. leaves senescence, shortens in grain filling period, reduction in photosynthesis and enhancing soluble sugars remobilization from grains to other vegetative organs are clear with water stress at the reproductive stage.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, the highest value of number of unfilled grains panicle-1 produced by ARD6-8-1-1-1-1-5 under drought treatment , while the lowest value of number of unfilled grains panicle-1 produced by Nerica 7 and Egyptian Yasmin under Normal irrigation. These results are in harmony with those stated by Hashem et al (2016), Zaman et al (2018) and Gewaily et al (2021) who reported that water deficit induced several changes in the structure and functional processes of reproductive organs in the rice, resulting to fluctuations in fertilization or premature abortion of the seed. leaves senescence, shortens in grain filling period, reduction in photosynthesis and enhancing soluble sugars remobilization from grains to other vegetative organs are clear with water stress at the reproductive stage.…”
Section: Resultssupporting
confidence: 92%
“…While, the lowest values of grain yield were obtained with Nerica 7 under water shortage with the highest percentage (33.63 %) of yield reduction compared to its production under normal irrigation . The results are inconformity with that stated by Kondhia et al (2015) and Gewaily et al (2021).…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation